Aptidão física relacionada a saúde de adolescentes iniciantes em um projeto de futebol - Pinheiro, Kenner Ohata Marques (Brasil, 2024)
he literature reports that physical fitness brings numerous health benefits, helping to prevent diseases, obesity and a sedentary lifestyle. Objective: the main objective of the study is to analyze the Health-Related Physical Fitness of adolescents starting a football project. Method: this is a descriptive study with a qualitative and quantitative approach. The sample was made up of 24 male children and adolescents, aged 12 to 16, participating in the CEF/ICSEZ/UFAM football project. Results: regarding the components Body Composition, Cardiorespiratory Fitness, Flexibility, they are in the healthy zone, except for the Abdominal Strength and Endurance component, which presents unsatisfactory indices, indicating physical inability. Conclusion: Adolescents are within a Health-Related Physical Fitness considered acceptable, as not all components are in the healthy zone. Therefore, it is necessary to encourage the practice of physical activity through sport, aiming to reduce the emergence of hypokinetic diseases, improving the performance and physical fitness of individuals in adolescence.